Improving virus diagnostics - International Potato Center (2016)
A Loop Mediated isothermal Amplification (LAMP) protocol for Sweet potato feathery mottle virus (SPFMV) was successfully tested in the field in Kakamega, Kenya utilizing a rapid extraction method and partially lyophilized reagents and enabled virus detection on site within 30 minutes. A fourth iteration of another diagnostic tool, ClonDiag arrays, was successfully tested at the Kenya Plant Health Inspectorate Service (KEPHIS) and a validation plan set up.